Thrombocytopenia in the nicu: new insights into causative mechanisms and treatments (Hematology Meeting Reports, 2009)
Thrombocytopenia affects 20-35% of neonates admitted to the NICU. Over the last decade, our understanding of the mechanisms underlying severe neonatal thrombocytopenia increased due to the development of non-invasive measures of thrombopoiesis suitable for use in neonates, including serum thrombopoietin (Tpo) concentrations, circulating megakaryocyte progenitors, and reticulated platelet percentages. The use of these tests in combination led to the recognition of different mechanisms underlying neonatal thrombocytopenia. In contrast to the progress made in understanding the pathophysiology of neonatal thrombocytopenia, therapeutic advances have been few. For most thrombocytopenic neonates, platelet transfusions remain the only therapy. However, there is a lack of scientific evidence to guide neonatal transfusion decisions, and studies to generate evidence-based guidelines for neonatal transfusions are needed.